PENGARUH SIFAT KEPRIBADIAN, KEPUASAN KERJA, PERILAKU WARGA ORGANISASI TERHADAP KOMITMEN ORGANISASI: STUDI KAUSAL PADA KARYAWAN PONDOK PESANTREN AL BAYAN DI KABUPATEN LEBAK - Iqbal Rosyid; Ade Jaya Sutisna (The Asia Pacific Journal Of Management Studies, 2025)
Specifically, the study explores the direct effects of personality traits, job satisfaction, and organizational citizenship behavior on organizational commitment.. Data were collected through a survey of 80 employees working at Pondok Pesantren Al Bayan, a faith-based educational institution with a unique organizational structure and work environment. The findings reveal that personality traits, job satisfaction, and organizational citizenship behavior have significant and positive effects on employees’ organizational commitment. Furthermore, personality traits were found to significantly influence both job satisfaction and the likelihood of displaying organizational citizenship behaviors. Theoretically, this study contributes to the literature by deepening the understanding of the pathways through which individual differences shape organizational commitment. From a practical standpoint, the research offers valuable insights for leaders at Pondok Pesantren Al Bayan in identifying personality-related factors that drive employee loyalty and dedication, as well as in fostering a work environment that promotes satisfaction and prosocial behavior. Overall, this study sheds light on why employees behave the way they do and under what circumstances such behaviors are most likely to emerge within a values-based institutional context.